Meningkatkan Kesejahteraan Pengrajin Gula Kelapa di Wilayah Kabupaten Purbalingga - Supomo Supomo (Economic Journal of Emerging Markets, 2007)
Small and medium industries/enterprises in this time are very strategic and have a role on the regional economic growth, it’s spread in entire villages and cities in Indonesia. it can afford to absorb the low layer of society, and it can afford to hold out in the long economy crisis during 9 years latest. As small and medium industries/enterprises have been facing many constraints, besides the Government does not have political will to develop them as society economy-based. The local government of Purbalingga now begins to pay attention to the people who have basic economy in particular of coconut palm sugar or small business (home industry) with the real regional economic development priorities program.Keywords: Small and Medium Industry, empowerment, people economy, local government policy.